Luigi Mangiagalli (Epidemiology, Biostatistics, and Public Health, 2022)
Luigi Mangiagalli (1850-1928) is a well known figure and a “founding father” of obstetrics and gynecology in Italy, but less recognized are the wide range implications of his work on a public health and social level. In fact, apart from its surgical, clinical and academic values, all the activities of Mangiagalli had a public health, and hence a political relevance. Thus, when at age 27 hewas named professor of Obstetrics and Gynecology in Sassari, Sardinia, he not only focused on the improvement of the local obstetrics clinic -when he arrived there were no beds and only a one broken forceps- and the control of puerperal infections, but also to the control of malaria and syphilis in pregnancy.